For God and globe : Christian internationalism in the United States between the Great War and the Cold War - Thompson, Michael G. (Michael Glenn) (Ithaca : Cornell University Press, 2015)
For God and Globe recovers the history of an important yet largely forgotten intellectual movement in interwar America. Michael G. Thompson explores the way radical-left and ecumenical Protestant internationalists articulated new understandings of the ethics of international relations between the 1920s and the 1940s. Missionary leaders such as Sherwood Eddy and journalists such as Kirby Page, as well as realist theologians including Reinhold Niebuhr, developed new kinds of religious enterprises devoted to producing knowledge on international relations for public consumption. For God and Globe centers on the excavation of two such efforts--the leading left-wing Protestant interwar periodical, The World Tomorrow, and the landmark Oxford 1937 ecumenical world conference. Thompson charts the simultaneous peak and decline of the movement in John Foster Dulles's ambitious efforts to link Christian internationalism to the cause of international organization after World War II. Concerned with far more than foreign policy, Christian internationalists developed critiques of racism, imperialism, and nationalism in world affairs. They rejected exceptionalist frameworks and eschewed the dominant "Christian nation" imaginary as a lens through which to view U.S. foreign relations. In the intellectual history of religion and American foreign relations, Protestantism most commonly appears as an ideological ancillary to expansionism and nationalism. For God and Globe challenges this account by recovering a movement that held Christian universalism to be a check against nationalism rather than a boon to it. -- Provided by publisher.
Introduction : missionaries, mainliners, and the making of a movement -- Anti-imperialism for Jesus -- The world tomorrow as a foreign policy counterpublic -- A funeral and two legacies -- All God's household -- Race, nation and globe at Oxford, 1937 -- Oxford's Atlantic crossing -- The Dulles Commission, the UN, and the Americanization of Christian internationalism -- Conclusion : neglected genealogies.
Includes bibliographical references and index.
Master record variable field(s) change: 050
Keywords: Christianity and international relations -- History -- 20th century; Christianity and politics -- United States -- History -- 20th century; Protestantism -- United States -- History -- 20th century; United States -- Church history -- 20th century; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; HISTORY -- United States -- 20th Century; Christianity and international relations; Christianity and politics; Protestantism; United States; 1900-1999; Electronic books; Church history; History